PERANAN H. TENGKU ILYAS DALAM MEMPERTAHANKAN DAN MENGISI KEMERDEKAAN DI RIAU 1947-1967 - Naim, Said Janatun; Isjoni, Isjoni; Asril, Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: H. Tengku Ilyas is one of the leading figures in defending and filling independence in Riau Province. H. Tengku Ilyas has many roles in maintaining and filling independence in Riau Province. The purpose of this research is to find out the life history of H. Tengku Ilyas, to find out the role of H. Tengku Ilyas before the colonial era, to know the role of H. Tengku Ilyas in maintaining independence, to find out the role of H. Tengku Ilyas in filling independence in the field of government. The results of this research are many contributions given by H. Tengku Ilyas during his lifetime. During the Netherlands colonial period, he was tasked with collecting taxes from the society to be submitted to the Netherlands. During the Netherlands Aggression II, he was assigned to become the Coordinator of the Districts of Kepenuhan and Tambusai, he was assigned to carry out defense and supplies preparation in the Tambusai area and Kepenuhan. After the Netherlands Aggression II ended many contributions of H. Tengku Ilyas in filling independence. One of them is becoming the Mayor of Pekanbaru. When he became Mayor, education began to increase, roads were widened and paved. The method used in this research is a historical research method which consists of four stages, namely heuristics, source criticism, interpretation and historiography. The data obtained from interviews were added with data obtained from books and archives. The data obtained from the results of interviews and literatures are then analyzed by my own language. The place of this research in writing scientific paper in Pekanbaru. The data collection techniques used were documentation, interviews and related literature in the role of the H. Tengku Ilyas figure in maintaining and filling independence in Riau Province.Key Words: Role, Fighters Figuree